HDX‐MS and deletion analysis of the type 4 secretion system protein TraF from the Escherichia coli F plasmid. Issue 3 (3rd February 2016) - Lento, Cristina; Ferraro, Michele; Wilson, Derek; Audette, Gerald F.
Abstract : Conjugative DNA transfer by the F‐plasmid is achieved through a type IV secretion system (T4SS) encoded within the plasmid's transfer region; TraF is one of several F‐T4SS proteins essential for F‐pilus assembly. In order to identify regions of the protein important for TraF function, a series of deletion mutants were assessed for their ability to recover conjugative transfer in a traF knockout. Interestingly, modification of any region of TraF abolishes pilus synthesis, resulting in a loss of rescue of conjugative function. Dynamic analysis of TraF by time‐resolved hydrogen–deuterium exchange revealed that the C‐terminal region containing the predicted thioredoxin‐like domain is quite structured, while the N‐terminal region, predicted to interact with TraH in the intact F‐T4SS, was more dynamic. Abstract :